vp_ip100811_elic_VerbalForms_OBJpl - Валентина Пуяковна Силкина (Надер); Ирина Пайковна Кошкарёва (Туглакова); Олеся Ханина (Bernard Comrie, 2010)
О.Ханина собирает с В.П.Надер лично-числовые окончания объектного спряжения для множественного объекта: аориста и прошедшего времени, на примере глагола duqa- 'потерять', рядом сидит И.П.Кошкарева и иногда подсказывает, потом она тоже садится к микрофону O.Khanina collects with V.P.Nader person-number affixes of object for plural object series: Aorist and Past, with the verb duqa 'to loose', there is I.P.Koshkarjova sitting nearby and saying something from time to time, then she also sits in front of the microphone Language_Name: Enets Language_Region: Asia Language_Country: Russia Project_Status: Complete Year: 2007 Start_Date: 2008-02-01 End_Date: 2011-01-31 Title vp_ip100811_elic_VerbalForms_OBJpl